A Test of the effectiveness of the ethyl acetate fraction of dayak onion bulbs (eleutherine bulbosa (mill.) urb) as an antihypertensive - Sari, Putri Nilam; Andika, Miming; Hasnita, Evi; Hasanah, Rizqa; Fitriani, Oriza Sativa; Putra, Fajrian Aulia; Rahmadasmi, Nola; Nanda, Nanda; Handayani, Tuti (Riset Informasi Kesehatan; Vol 13 No 1 (2024): Riset Informasi Kesehatan, 2024)
Hypertension is a condition where blood pressure exceeds normal limits, where systolic blood pressure is above 140 mmHg and diastolic blood pressure is above 90 mmHg. One plant that can lower blood pressure is Dayak onion bulbs. The aim of this study was to determine the effectiveness of the ethyl acetate fraction of Dayak onion bulbs (Eleutherine bulbosa (Mill) Urb) in reducing blood pressure in hypertensive male white rats. The method was experimental, using 36 male white rats, divided into 6 groups, namely negative control, positive control, dose group (50, 100, 200 mg/kgbb) and comparison group (catopril). The inducer used was 8% NaCl for 14 days. Blood pressure measurements are carried out using a Non-Invasive Blood Pressure (NIBP) device. Data analysis used One Way Anova and continued with the Duncan test. The results showed that administration of Dayak onion bulb ethyl acetate fraction had an effect on reducing systolic, diastolic, mean arterial blood pressure and heart rate significantly (p<0.05). The conclusion shows that the effective dose in reducing blood pressure is administration of the ethyl acetate fraction at a dose of 200 mg/kgbb. There was a histopathological improvement in the thickness of the left ventricular muscle in mice.